Avaliação da assistência ao paciente e/ou diabético na Estratégia Saúde da Família - Carregã, Karyn [UNESP] (2014)
The Family Health Strategy, the result of the attempt to reorganize the Basic Attention, aims to strengthen the guidelines and principles of the Unique Health System and answer to the real health needs of the users that seek for this care, among them, the patients with hypertension and/or Diabetes Mellitus, diseases that are exponentially growing, becoming a great problem of public health, thus, the necessity of running studies that evaluate the quality of the services that attend this population highlights. By the former exposed this study was developed, presenting a quanti-qualitative approach, focused on the evaluation of the health assistance quality and its relation with the perception of the hypertension and Diabetes Mellitus bearer and the professionals of the family health team. The theoretical referential adopted was the one described by Donabedian and the methodological referential was the Collective Subject Speech to analyze the qualitative data. We evidenced expressive precariousness in the structure of the Family Health Unit regarding human resources, obtaining a medium quality score of 69,4, where 77,7% of the units presented insufficient number of Health Community Agents. We identified fragilities in the caring process, both in the quality of the organizing process, and patient clinical records related to the anamnesis and physical exams, the medium evaluated score was 43,8. However, the patients and health professionals evaluated the caring as satisfactory, despite the related difficulties in the speech of the team regarding the assistance. It was identified a significant positive correlation between the caring process score and the perception of the professionals regarding the USF structure. We noted that the Family Health Strategy is surrounded by fragilities, being necessary a reformulation in the mode of action of the teams that provide assistance to the population, besides, as showed in this study, an adequacy in the ...